Social approach behaviors are similar on conventional versus reverse lighting cycles, and in replications across cohorts, in BTBR T+ tf/J, C57BL/6J, and vasopressin receptor 1B mutant mice - Yang, Mu; Scattoni, Maria L.; Zhodzishsky, Vladimir; Chen, Thomas; Caldwell, Heather; Young, W S.; McFarlane, Hewlet G.; Crawley, Jacqueline N. (Frontiers in Behavioral Neuroscience, 2007)
Mice are a nocturnal species, whose social behaviors occur primarily during the dark phase of the circadian cycle. However, laboratory rodents are frequently tested during their light phase, for practical reasons. We investigated the question of whether light phase testing presents a methodological pitfall for investigating mouse social approach behaviors. Three lines of mice were systematically compared. One cohort of each line was raised in a conventional lighting schedule and tested during the light phase, under white light illumination; another cohort was raised in a reverse lighting schedule and tested during their dark phase, under dim red light. Male C57BL/6J (B6) displayed high levels of sociability in our three-chambered automated social approach task when tested in either phase. BTBR T+ tf/J (BTBR) displayed low levels of sociability in either phase. Five cohorts of vasopressin receptor subtype 1b (Avpr1b) null mutants, heterozygotes, and wildtype littermate controls were tested in the same social approach paradigm: three in the dark phase and two in the light phase. All three genotypes displayed normal sociability in four out of the five replications. In the juvenile play test, testing phase had no effect on play soliciting behaviors in Avpr1b mice, but had modest effects on nose sniff and huddling. Taken together, these findings indicate that testing phase is not a crucial factor for studying some forms of social approach in juvenile and adult mice.